2005
DOI: 10.1016/j.expneurol.2005.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Myelin-associated glycoprotein and complementary axonal ligands, gangliosides, mediate axon stability in the CNS and PNS: Neuropathology and behavioral deficits in single- and double-null mice

Abstract: Complementary interacting molecules on myelin and axons are required for long-term axon-myelin stability. Their disruption results in axon degeneration, contributing to the pathogenesis of demyelinating diseases. Myelin-associated glycoprotein (MAG), a minor constituent of central and peripheral nervous system myelin, is a member of the Siglec family of sialic acid-binding lectins and binds to gangliosides GD1a and GT1b, prominent molecules on the axon surface. Mice lacking the ganglioside biosynthetic gene Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
151
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(160 citation statements)
references
References 56 publications
7
151
1
1
Order By: Relevance
“…NCmahTg mice exhibited hyperactivity throughout the test time in this study (Fig. 8F), consistent with a previous report showing that Mag-null and B4galnt1-null mice were reported to be hyperactive (49). Basal pain response was also assessed given that it can be mediated by myelinated axons.…”
Section: Loss Of Myelin-associated Glycoprotein (Mag) Ligand and Abnosupporting
confidence: 78%
“…NCmahTg mice exhibited hyperactivity throughout the test time in this study (Fig. 8F), consistent with a previous report showing that Mag-null and B4galnt1-null mice were reported to be hyperactive (49). Basal pain response was also assessed given that it can be mediated by myelinated axons.…”
Section: Loss Of Myelin-associated Glycoprotein (Mag) Ligand and Abnosupporting
confidence: 78%
“…In support of this perception, it has been reported that a disruption of synthesis of complex gangliosides in axons of mice leads to an interruption of the interaction of gangliosides with complementary lectin-binding partners, e.g., myelin-associated glycoprotein, months after birth (27). In this study, the morphologic sequelae were axon degeneration.…”
Section: Discussionmentioning
confidence: 76%
“…There is no indication of any sex-specific effect of the MAG gene [38], so our groups included both sexes. We also included one heterozygote mouse in our wildtype control group, because there is no indication of a heterozygote phenotype [33].…”
Section: Discussionmentioning
confidence: 99%
“…Selected because of its decreased expression levels [1,2,22] and impaired hindlimb reflex extension [38]. However, the mutant mice showed no differences in spatial learning and memory or in swimming speed, as demonstrated by a Morris water maze test [37].…”
Section: Introductionmentioning
confidence: 99%